2020
DOI: 10.1088/1742-6596/1700/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of student satisfaction of e-learning using the end-user computing satisfaction method during the Covid-19 pandemic

Abstract: The government’s physical distancing policy to prevent transmission of the covid19 virus caused changes in learning patterns from face-to-face learning to distance education. The application of distance education at Universitas Negeri Yogyakarta is one of them through e-learning. Measurement of the level of e-learning user satisfaction is an assessment of the success of e-learning itself. The method used to measure students’ level of satisfaction using e-learning is End-User Computing Satisfaction (EUCS). EUCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
2
10
0
1
Order By: Relevance
“…Although in most of the studies, the group of variables used were not the same as in the current study, findings however provide useful comparison with the current study. For example, findings from the current study corroborate previous studies that have reported significant relationship between satisfaction and each of attitude (Kovačević et al 2021 ), motivation (Hettiarachchi et al 2021 ; Rahman et al 2021 ), ease of use (Prasetya et al 2020 ; Agyeiwaah et al 2021 ; Han and Sa 2021 ; Jiang et al 2021 ; Kovačević et al 2021 ), self-efficacy (El-Sayad et al 2021 ; Jiang et al 2021 ) and cognitive engagement (Roque-Hernández et al 2021 ; Trisanti et al 2021 ).…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Although in most of the studies, the group of variables used were not the same as in the current study, findings however provide useful comparison with the current study. For example, findings from the current study corroborate previous studies that have reported significant relationship between satisfaction and each of attitude (Kovačević et al 2021 ), motivation (Hettiarachchi et al 2021 ; Rahman et al 2021 ), ease of use (Prasetya et al 2020 ; Agyeiwaah et al 2021 ; Han and Sa 2021 ; Jiang et al 2021 ; Kovačević et al 2021 ), self-efficacy (El-Sayad et al 2021 ; Jiang et al 2021 ) and cognitive engagement (Roque-Hernández et al 2021 ; Trisanti et al 2021 ).…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…If technology tools and platforms deployed in online teaching are perceived easy to use, students may achieve higher satisfaction as a result. More studies have shown perceived ease of use or digital competencies as an indicator of satisfaction with online delivery (Prasetya et al 2020 ; Kovačević et al 2021 ). The more learners perceive technology platforms deployed for ERT as easy to use, the stronger their willingness to use them and the higher their satisfaction with ERT.…”
Section: Factors Influencing Students’ Satisfaction With Ertmentioning
confidence: 99%
“…Variabel content akan melihat hasil kepuasan dalam hal tampilan dan juga informasi yang disediakan dalam E-learning [14]. Variabel accuracy akan mengukur kepuasan pengguna pada keakuratan atau ketepatan sistem dalam mengolah input dan output serta dalam pemrosesan data [15].…”
Section: Pendahuluanunclassified
“…The EUCS instrument was used to measure users' satisfaction on Malaysian government's electronic systems [16], to evaluate the Brazilian Financial Administration's integrated system [17], and to analyze the satisfaction on Indonesia's Customs & Excise Information System and Automation [18]. EUCS was also applied for web-based information system [19], website [20][21][22], disaster mitigation information system [23], security system [24], police information system [25], voter data information system [26], government financial system [27], computerized accounting system [28,29], accounting information system [30,31], office information system [12], hospital and health care information system [14,[32][33][34][35][36][37], education or academic information system [38][39][40][41], e-learning or learning management system [42][43][44][45][46][47][48][49][50], online library [51], university grading system [11], university tuition fee system [52], conference management system [53], enterprrise resource planning system [15,…”
Section: Introductionmentioning
confidence: 99%